Catholicity Without Leviathan: Stanley Hauerwas's Perspective on the Church as an Alternative Political Community. Issue 1 (30th July 2018) - Untea, Ionut
Abstract: The article brings into focus a series of political arguments of Stanley Hauerwas's "theological politics" and argues that these arguments are in stark contrast with the theoretical perspective of a political rule by a god-like Leviathan, an image inherited in modern and contemporary political culture from the early modern English philosopher Thomas Hobbes. The first section focuses on Hauerwas's arguments regarding the political potential of the term "Catholicity" to represent an alternative to the coercive politics reinforced by the post-Enlightenment nation state. The second section proposes a reflection on the way the Church's Catholicity may be expressed politically without falling into the temptation of involving the Leviathan to sort out the issues generated by its diversity. The concluding section illustrates how Hauerwas uses his approach of a universal unity of Christians "without Leviathan" in his exhortation addressed to American Christians to say "no" to Donald Trump's version of communal unity that is rather based on "total allegiance" to the United States and on "repressive politics".